1972
DOI: 10.1111/j.1748-1716.1972.tb05323.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Training on Esterified Fatty Acids and Carnitine in Muscle and on Lipolysis in Adipose Tissue in Vitro

Abstract: The concentration of triglycerides, phospholipids and carnitine was determined in red and white parts of the gastrocnemius muscle from rats with and without a period of training by running. Also the rate of lipolysis in adipose tissue was determined with and without stimulation in vitro. The concentration of triglycerides was reduced in the red and white muscle tissue but positively correlated to each other in white muscle tissue. This suggests that the white muscle tissue. Correlation analysis revealed no dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

1974
1974
2005
2005

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 27 publications
1
10
1
Order By: Relevance
“…Data are mean ± SD ES Effect size (difference between means divided by the SD of the untrained group); MUFA monounsaturated fatty acids; PUFA polyunsaturated fatty acids; ND not detected; U/S unsaturated/ saturated; UI unsaturation index *Significantly different from untrained (P<0.05) a Indices of enzyme activity were calculated from the sum of the concentration of each fatty acid in PL and TG Concerning muscle, its total TG content was greatly reduced with training. Most of the relevant studies have found decreases (Froberg et al 1972;Kaciuba-Uscilko et al 1981;Oscai et al 1982), although no differences between trained and untrained rats have also been reported (Lee et al 2002). The reduction found in the present study (by 75%) was larger than the ones found in the soleus (32%) and EDL (34%) of the same animals , suggesting a greater responsiveness of gastrocnemius muscle TG to training.…”
Section: Discussioncontrasting
confidence: 75%
“…Data are mean ± SD ES Effect size (difference between means divided by the SD of the untrained group); MUFA monounsaturated fatty acids; PUFA polyunsaturated fatty acids; ND not detected; U/S unsaturated/ saturated; UI unsaturation index *Significantly different from untrained (P<0.05) a Indices of enzyme activity were calculated from the sum of the concentration of each fatty acid in PL and TG Concerning muscle, its total TG content was greatly reduced with training. Most of the relevant studies have found decreases (Froberg et al 1972;Kaciuba-Uscilko et al 1981;Oscai et al 1982), although no differences between trained and untrained rats have also been reported (Lee et al 2002). The reduction found in the present study (by 75%) was larger than the ones found in the soleus (32%) and EDL (34%) of the same animals , suggesting a greater responsiveness of gastrocnemius muscle TG to training.…”
Section: Discussioncontrasting
confidence: 75%
“…On the other hand, Hurley et al (1986) found no significant difference between pre-and post-training muscle TG concentrations in subjects who underwent an intensive 12-week running and cycling training programme. Confounding results have been found in studies on the rat, where both a decrease (Froberg, 1971;Froberg et al 1972) and no change (Gorski & Kiryluk, 1980) in muscle TG concentration in response to training have been noted.…”
Section: U T I L I Z a T I O N O F P L A S M A -D E R I V E D T R I Amentioning
confidence: 89%
“…Suzuki et al (32) found that urinary excretion of carnitine was increased slightly with heavy running exercise in humans. Froberg et al (17) noted elevated carnitine concentrations in the red portion of gastrocnemius muscle of rats subjected to 15 weeks of treadmill running. These results suggest that carnitine utilization may be increased by exercise but a functional defi ciency is not manifested, perhaps due to an increased synthetic rate of carnitine by the exercising animal.…”
Section: Discussionmentioning
confidence: 99%